KAJIAN KONVERSI LAHAN SAWAH TADAH HUJAN MENJADI PERKEBUNAN KELAPA SAWIT DI JORONG ANAK AIR KUMAYAN KENAGARIAN KAMPUNG TANGAH KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Suryani, Irma; Rianto, Slamet; Yuherman.SP, Yuherman.SP (Pendidikan Geografi, 2014)
Â ABSTRACTThis Research aimto get information and data that is 1) Income 2) Knowledge 3) Management about Study Convert Farm Wet Ricefield to Become Plantation of Coconut of Sawit in Jorong Anak Air Kumayan Kenagarian Kampung Tangah Kecamatan Lubuk BasungÂ  Kabupaten Agam. This Type Research is descriptive, which become research population is the overall of family head in Anak Air Kumayan Kenagarian Kampung Tangah Kecamatan Lubuk Basung Kabupaten Agam, consisting of some Dusun that is: Dusun Durian Gadang, Dusun Masang,Dusun Tarantang. Sampel taken totally sampling that is equal to 47 amount of Family Head exist in Dusun Masang and Dusun Tarantang which Converting Farm Wet ricefield dependant to rain in Jorong Anak Air Kumayan Kenagarian Kampung Tangah Kecamatan Lubuk Basung Kabupaten Agam. Result of this research indicate that 1) Income of family head in converting wet ricefield dependant to rain farm become plantation of coconut of sawit this can be seen in general family headanswer Rp. 1.000.000- Rp1.900.000 per month for food counted 38 people 80,85% and to the non food counted 19 family head 40,42% from 47 responder family head which replying. 2)Knowledge of family head in converting wet ricefield dependant to rain farm become plantation of coconut of sawit seen in general family head [reply/ answer] have understood how to determine fruits which have ready for in this crop can be seen [by] family head [reply/ answer] its fruit have formed colour of black counted 47 family head 100% from 47 responder which replying.3) Management of family head in converting wet ricefield dependant to rain farm become plantation of coconut of sawit, can be seen in general family head in conservancy of coconut of sawit their only just sprayinganswer21 people 44,68% from 47 responder which replying.